2015
DOI: 10.1519/jsc.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screen for Predicting Running Injuries in 18- to 24-Year-Old Competitive Male Runners

Abstract: The purpose of this study was to investigate whether the functional movement screen (FMS) could predict running injuries in competitive runners. Eighty-four competitive male runners (average age = 20.0 ± 1.1 years) participated. Each subject performed the FMS, which consisted of 7 movement tests (each score range: 0-3, total score range: 0-21), during the preseason. The incidence of running injuries (time lost because of injury ≤ 4 weeks) was investigated through a follow-up survey during the 6-month season. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 14 publications
(15 reference statements)
3
69
0
1
Order By: Relevance
“…This allows for the actual risk factor to be addressed and mitigated more accurately. Recent research in competitive male runners has shown that a combination of deep squat and active straight leg raise scores were predictive of injury, but the FMS composite score was not (21).…”
Section: Since Kazman Et Al (2014) Found That the Fms Test Is Not Amentioning
confidence: 94%
See 2 more Smart Citations
“…This allows for the actual risk factor to be addressed and mitigated more accurately. Recent research in competitive male runners has shown that a combination of deep squat and active straight leg raise scores were predictive of injury, but the FMS composite score was not (21).…”
Section: Since Kazman Et Al (2014) Found That the Fms Test Is Not Amentioning
confidence: 94%
“…Recently published research by Hotta et al, (2015) showed that in a population of competitive male runners the composite FMS score was not predictive of injury, but a combination of the scores for the deep squat and active straight leg raise tests was (21). Based on this finding it seems that certain FMS component tests may be more relevant for injury risk than others within particular populations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The additional aim of present study was to analyse relationships between the cycling specific postural stability during pedalling at different intensity levels and FMS score that describes the cyclists' core stability and fundamental movement abilities in body control (Cook et al, 2014a). The results of FMS test indicated that less than half (n=16) of the cyclists achieved score of 14 points or less, that is found to be a line for elevated injury risk (Kiesel et al, 2007;Hotta et al, 2015). The moderate to strong relationships between cycling postural stability and FMS score directed also that cyclists with low core stability and pure ability to control his body are moving more in the saddle.…”
Section: Discussionmentioning
confidence: 99%
“…The FMS test includes 7 fundamental movement exercises that are evaluated in the terms of the quality of movement patterns, bilateral symmetry and existence of the compensatory movements in a scale from 0 to 3 with a maximal overall score of 21 points (Cook et al, 2014a and. This test complex is shown to have a good intraand interrater reliability (Minick et al, 2010;Teyhen et al, 2012) and validity as a predictor of injury risk (Kiesel et al, 2007;Hotta et al, 2015 ). Validity of the FMS to predict sport performance and ability to perform sports specific movement correctly is not so clear as demonstrated with the risk of injuries (Kraus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%